An Initial Study of Ultra High Performance Concrete as Reusable Mold Material for Aluminum Casting - Link, Janna; Teichmann, Fabian; Wetzel, Alexander; Müller, Sebastian; Middendorf, Bernhard (Materials, 2025)
The initial investigation evaluates the feasibility of ultra high performance concrete (UHPC) as a material for reusable molds in aluminum casting. Two specific UHPC formulations were investigated: one based on ordinary Portland cement (OPC) and another utilizing alkali-activated materials (AAM). The study focused on investigating the surface through roughness measurements and the thermal durability through repeated casting cycles. The thermal stability of the molds was investigated by thermogravimetric analysis, mercury intrusion porosimetry, crack segmentation, optical microscopy, and electron microscopy. Results indicate that molds fabricated from AAM-UHPC exhibit relatively better performance in terms of maintaining structural integrity and surface quality over repeated uses. AAM-UHPC molds were able to withstand up to ten casting cycles with acceptable surface degradation and no significant failure, while OPC-UHPC molds exhibited a faster degradation under similar conditions. Microstructural changes and the interaction of UHPC materials with molten aluminum were investigated, highlighting the low adhesion and defect formation. Additionally, the molds demonstrated sound casting quality, with a grain size comparable to that achieved using traditional steel molds ( 90 µm), underscoring the potential of UHPC materials for enhancing casting quality and efficiency. The study concludes that UHPC, particularly with alkali-activated formulations, shows promise for low-pressure casting environment
Keywords: reusable mold casting; UHPC; surface characterization; aluminum; alkali-activated materials; die soldering

Investigations on Dual Laser Beam Welding of Aluminium High Pressure Die Castings at Reduced Ambient Pressure (403) (Peer Reviewed) - Teichmann, Fabian; Müller, Sebastian; Dilger, Klaus (ICALEO 2018, 2018)

Investigations on dual laser beam welding of aluminum high pressure die castings at reduced ambient pressure - Teichmann, Fabian; Müller, Sebastian; Dilger, Klaus (Journal of Laser Applications, 2018)
During the manufacture of aluminum high pressure die castings, the aluminum alloy is in a liquid phase during the majority of process steps. Due to the high solubility of hydrogen in liquid aluminum, the die casted part likely has an increased hydrogen content, which affects the weldability negatively. When welding these materials, hydrides dissociate and hydrogen is liberated and forms porosity during solidification. To avoid the described formation of porosity, friction stir welding below the melting point and electron beam welding with high frequency beam oscillation were investigated in prior research. Other studies reported that the formation of porosity during laser beam welding of pure aluminum was prevented by the application of dual beam configurations. However, it is well known that laser beam welding under vacuum condition has several advantages, such as the increase in penetration depth, the enhanced degasification, or the overall calming effect on the melt pool when welding ferrous metals. Aiming to combine these advantages, the current work consequently focuses on the occurrence of porosity during dual laser beam welding of aluminum die castings under vacuum (100–0.1 hPa) and atmospheric conditions. All results are based on the outcome of x-ray computed tomography or tensile testing.
Keywords: aluminium alloys; aluminium alloys; computerised tomography; die casting; laser beam welding; oscillations; tensile testing; computerised tomography; die casting; laser beam welding; oscillations; tensile testing

Laser beam welding of highly ductile secondary HPDC Aluminium Alloy at reduced ambient pressure - Teichmann, Fabian; Müller, Sebastian; Börner, Christian; Pries, Helge; Dilger, Klaus (METALL ITAL, 2016)
Keywords: Aluminium-Druckguss; Druckguss; Laserstrahlschweißen; Unterdruck; Vakuum

Linear Elastic FE-Analysis of porous, laser welded, heat treatable, aluminium high pressure die castings based on X-ray computed tomography data - Teichmann, Fabian; Ziemer, Arne; Leitner, Martin; Hensel, Jonas; Dilger, Klaus (Materials, 2020)
The welding of aluminium high pressure die castings is a well known and broadly investigated challenge in various fields of industry and research. Prior research in this specific field mainly focused on the optimisation of the welding and the casting process and on the cause of the frequently occurring porosity and incomplete fusion phenomena, whereas the impacts of these defects have hardly been addressed. Therefore, the underlying study presents the investigation of weldments in EN AC-AlSi10MnMg high pressure aluminium die castings by linear elastic finite element analysis based on X-ray computed tomography as a novel approach. Hereby, four laser weldments with differing surfaces and pore contents were investigated by X-ray computed tomography and tensile testing. Based on the voxel datasets of the porous weldments, triangular finite element meshes were generated and a numerical finite element analysis was conducted. Good agreement of the stress-strain curves between the simulations and the experiments was achieved.
Created from Fastlane, Scopus look-up
Keywords: AC-AlSi10MnMg; Aluminium; Finite elements; High pressure aluminium die casting; Laser welding; Mesh; Structural simulation; X-ray computed tomography

(untitled) - Pohl, Marco; Teichmann, Fabian; Hensel, Jonas; Dilger, Klaus (DVS Congress 2020)

Möglichkeiten zur automatisierten Bestimmung von Schweißnahtunregelmäßigkeiten und -geometrie mittels 3D-Computertomographie - Ziemer, Arne; Teichmann, Fabian; Hensel, Jonas; Dilger, Klaus (DVS Berichte Band 344, 2018)

Multiple Spot Electron Beam Welding of Aluminium Die Castings - Teichmann, Fabian; Pries, Helge; Dilger, Klaus (72nd World Foundry Congress (WFC 2016), 2016)

On the occurrence of weld bead porosity during laser vacuum welding of high pressure aluminium die castings - Teichmann, Fabian; Müller, Sebastian; Dilger, Klaus (Procedia CIRP, 2018)
Procedia CIRP, 74 (2018) 438-441. doi:10.1016/j.procir.2018.08.163
Keywords: Aluminium; Aluminium die castings; Laser vacuum welding; Laser Welding; Porosity; X-ray computed tomography

Schweißnahtgüte und Schwingfestigkeit lasergeschweißter Verbindungen aus Aluminium Knet- und Druckgusswerkstoffen - Keßler, Benjamin; Dittrich, Dirk; Jahn, Axel; Teichmann, Fabian; Hensel, Jonas; Dilger, Klaus; et al. (DVS Congress 2022, 2022)

Strahlschweißen von verzinkten Stahlblechen im Überlappstoß ohne voreingestellten Entgasungsspalt unter Anwendung unterschiedlicher Strahlformungsmethoden - Tóth, Tamás; Teichmann, Fabian; Dilger, Klaus (Schweissen und Schneiden, 2022)

(untitled) - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (Zbornik povzetkov referatov 56. mednarodnega livarskega posvetovanja, Portorož)

The influence of ambient pressure during laser beam welding of aluminium high pressure die castings on the occurrence of weld bead porosity - Teichmann, Fabian; Müller, Sebastian; Dilger, Klaus (Lasers in Manufacturing 2017, 2017)

Thermo-Mechanical Optimization of Die Casting Molds Using Topology Optimization and Numerical Simulations - Djabraian, Serouj; Teichmann, Fabian; Müller, Sebastian (Materials, 2024)
Conventional cooling channels used in die casting molds exhibit significant drawbacks, resulting in extended cooling times for cast parts. Issues such as the formation of dirt, limescale, and corrosion substantially diminish the thermal efficiency of these channels, leading to challenges in achieving uniform cooling and potential quality issues. In response to these challenges, this study proposes Topology Optimization as a novel approach. It involves designing cooling structures through Topology Optimization to replace traditional cooling channels, incorporating both Discrete and Gaussian boundary conditions to optimize thermal efficiency. Additionally, Structural Topology Optimization is employed to ensure structural integrity, preventing deformation or yielding under high loads during the die casting process. Numerical analysis revealed superior thermal performance compared to conventional channels, particularly when subjected to Discrete and Gaussian boundary conditions. Furthermore, the application of the latter establishes conformal cooling and minimizes temperature gradients in the casting, reducing casting defects such as shrinkage porosity. These findings highlight the efficacy of Topology Optimization in addressing the challenges of traditional cooling methods, with wide-ranging implications for manufacturing processes utilizing permanent molds for shaping materials.
CRIS-Team Scopus Importer:2024-05-24
Keywords: COMSOL multiphysics; cooling structures; die casting; heat sink; mold; structural optimization; thermal optimization; topology optimization

(untitled) - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (DVS Congress 2016)

(untitled) - Teichmann, Fabian; Köhler, Markus; Pries, Helge; Dilger, Klaus (36. Assistentenseminar Füge- und Schweißtechnik)

Verringerung der Porenbildung beim Laserstrahlschweißen von Aluminium-Druckgusslegierungen durch reduzierten Umgebungsdruck und Doppelfokustechnik - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (Giesserei, 2017)

Verringerung der Porenbildung beim Laserstrahlschweißen von Aluminium-Druckgusslegierungen durch reduzierten Umgebungsdruck und Doppelfokustechnik - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (Schweissen und Schneiden, 2018)

(untitled) - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (DVS Berichte)

(untitled) - Teichmann, Fabian; Müller, Sebastian; Pries, Helge; Dilger, Klaus (Laser- und Elektronenstrahlschweißen von Aluminiumwerkstoffen)